Interpersonal and Digital Communication in Supporting Midwifery Education for the Community in Percut Sei Tuan Deli Serdang Village - Nugraeny, Lolita; Mahriyuni, Mahriyuni (UMSU, 2025)
This study aims to analyze the role of interpersonal and digital communication in supporting midwifery education for the community in Percut Sei Tuan Village, Deli Serdang. The research method used was qualitative descriptive with in-depth interview techniques with midwives, midwifery students, and marginalized communities. The results of the study show that interpersonal communication between midwives and the community plays an important role in building trust and understanding about maternal and child health. Meanwhile, the use of digital media such as WhatsApp and social media is able to expand the reach of midwifery education, although it still faces obstacles to access to technology. The conclusion of this study confirms that the integration of interpersonal and digital communication can increase the effectiveness of midwifery education in marginalized communities.